Smanjenje štetnosti ispušnih plinova dizelskog motora - Golubić, Jasna; Štrumberger, Nada (Promet - Traffic&Transportation, 2012)
The paper deals with some possibilities of reduction of Diesel engine exhaust emission hazards. For purposes of purification of exhaust emissions, the in-built filters can be provided, like ceramic filters for sooth and water filters for gases. The oxidation catalyst may also be provided in addition to filters. Hybrid systems have been tested in ’Golf’ automobiles i.e. the combination of internal combustion engine and electric drive. This vehicle has been named ’Eco Golf’. A mixture of Diesel fuel and n-butanol in the ratio of 60:40 has been used as the alternative fuel introducing the reduction of NOx by 8% and of particles by 36%. All limit values of Diesel engine exhaust gas components have been given in ECE R49 test.